PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS WEB - Moh Fahri Yasin; Wishnu Sasongko (Akademika, 2016)
This study aims to provide an overview of the development of web-based learning model. Stageby stage has been passed so well that the product will always maintained its quality because it is madeby prioritizing process.From the early stages, the formulation stage to the final stage which is the stage of utilization analysis.All done and well planned. This development attention on every detail of every phase of Dick and CareyModel, because a good process will produce a good learning media anyway. Although only as analternative to learning, web-based learning program is expected this could make a positive impact forthe future of learning in Education Technology.From the aspect of quality of content and learning objectives in the program obtained value of 4.00 andthis number is expressed quite well. Then from the aspect of quality instructional, get the value of 4.00which means that the quality is also good. In the following aspects of technical quality scored 4.50 andis stated to have the technical quality was quite good. For the overall value of the experts, the programhas gained value of 4.17 so stated this product is quite good.From the aspect of quality of content and learning objectives in the program obtained value of 4.00 anda number have otherwise been good. Then, from a quality instructional program is to get a value of4.75 which means that instructional quality is also good. In the following aspects of technical qualityscored 4.50 and the web is stated to have the technical quality is good. For the overall value of the user,then this program obtain a value of 4.42 so stated this product is quite good